2019
DOI: 10.1108/acmm-10-2018-2013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced corrosion resistance of Cr-Mn ASS by low temperature salt bath nitriding technique for the replacement of convectional Cr-Ni ASS

Abstract: Purpose The purpose of this paper is to enhance the corrosion resistance of Cr-Mn austenitic stainless steel (ASS) via low temperature salt bath nitriding and to replace the convectional Cr-Ni ASS with newly developed enhanced corrosion resistive Cr-Mn ASS. Design/methodology/approach The low temperature salt bath nitriding was performed on Cr-Mn ASS at 450°C for 3 h in potassium nitrate salt bath. Findings The present paper compares the corrosion resistance of salt bath nitrided Cr-Mn ASS with convectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…6. In Bode plots, the impedance modulus at low-frequency region signifies the resistance to corrosion, while the higher impedance values at high-frequency region signify the passive film compactness [31,32]. Similar to the Nyquist plots, the higher impedance values can be seen for 316L BM, while the least can be observed for 201 austenitic SS BM.…”
Section: Tensile Measurementmentioning
confidence: 69%
See 2 more Smart Citations
“…6. In Bode plots, the impedance modulus at low-frequency region signifies the resistance to corrosion, while the higher impedance values at high-frequency region signify the passive film compactness [31,32]. Similar to the Nyquist plots, the higher impedance values can be seen for 316L BM, while the least can be observed for 201 austenitic SS BM.…”
Section: Tensile Measurementmentioning
confidence: 69%
“…It has been reported that higher the E pit values, higher is the corrosion resistance. Hence, the better corrosion resistance of 316L austenitic SS can be attributed to the higher alloying elements (Mo and Ni) as more compared to 201 austenitic SS [31]. Interestingly, it can be noticed from Table 4 that the E pit values for LHI FZ and HHI FZ are higher than the 201 austenitic SS BM.…”
Section: Potentiodynamic Polarization Testmentioning
confidence: 91%
See 1 more Smart Citation
“…On one hand, the use of Ni is preferable compared to Mn not only in terms of an austenitic phase stabilizer, but also due to its contribution to increasing the corrosion resistance of SSs, especially in acidic environments. On the other hand, nickel’s high and fluctuating price cannot be neglected, consequently influencing that of SSs; thus, new strategies in the development of new alloys containing Mn are proposed [ 46 ] and could be promoted.…”
Section: Substitution and Saving Of Chromium In Stainless Steelmentioning
confidence: 99%
“…A promising strategy in the direction of saving Cr and maintaining the corrosion performances of the most common SSs is that which considers the development of new Fe-based alloys. They have a low-Cr content in the bulk (e.g., low-alloyed common steels or some ferritic SSs), whereas the surface has a Cr-rich coating [ 21 ] and/or other protective coating solutions [ 47 ], containing in the bulk Mn [ 46 ] in place of Ni. Through laser and plasma technologies or ion implantation, a surface alloying of Cr or Cr, C, N, etc.-rich surfaces can be obtained as reported by the following examples.…”
Section: Substitution and Saving Of Chromium In Stainless Steelmentioning
confidence: 99%